Information System Design of River Water Quality in Lampung Province through Personal Extreme Programming Method - Tri Sandika; Henry Kurniawan (Jurnal Ilmiah ESAI, 2014)
Water is vital natural resource for human and other living creatures as well as the capital for development. Nowadays, the need of clean water both quality and quantity increase sharply due to the increase of population. Although Indonesia is known to have 6% of world water resources or 21% of Asia Pacific, the scarce of water availability increase every year. The tendency of water consumption increases exponentially while the water availability decreases due to natural destruction and pollution. Similar condition also happens in Lampung province. Even though Lampung has some potentials of water resources, the problem of getting clean water appears in some places. To handle the problem, it is needed a system that can inform river water quality in Lampung so that the society can use and reserve the water resource. With Personal Extreme Programming (PXP) method, the development of water quality information system can be developed fast and effectively. The output of this research is the river water quality information system in Lampung Province.Key word : water quality, information system, PXP